Manifestations of climatic teleconnections in Czech drought characteristics - Mikšovský, J. (Jiří); Trnka, M. (Miroslav); Brázdil, R. (Rudolf) (2016)
Occurrence and intensity of droughts are governed by a multitude of factors, including the effects of large scale weather and climate variability patterns. Of particular interest regarding the meteorological droughts are the manifestations of climate oscillatory modes, associated not only with atmospheric circulation, but also with ocean dynamics and their mutual interactions. Recent studies dealing with attribution of central European drought characteristics have highlighted several possible links to internal climate oscillations, originating from the nearby north Atlantic area, but also from the Pacific. In this study, the analysis of these teleconnections is further extended. Using multivariable regression analysis applied on indices expressing mid-term drought we demonstrate that prominence of components related to the phase of Pacific Decadal Oscillation generally surpasses that of El Niño – Southern Oscillation. It is also shown that noteworthy deviations from linearity exist in the drought responses, as revealed by dependence of the regression coefficients on the phase of the oscillations. Altogether, our results confirm the potentially high relevance of trans-planetary teleconnections in the context of central European climate, and they also encourage future attention to the nonlinearities in the responses to the climate drivers.